A Comprehensive Microscopic Picture of the Benzhydryl Radical and Cation Photogeneration and Interconversion through Electron Transfer. Issue 7 (28th March 2013) - Sailer, Christian F.; Thallmair, Sebastian; Fingerhut, Benjamin P.; Nolte, Christoph; Ammer, Johannes; Mayr, Herbert; Pugliesi, Igor; de Vivie‐Riedle, Regina; Riedle, Eberhard
Abstract Bond cleavage and bond formation are central to organic chemistry. Carbocations play a key role in our understanding of nucleophilic substitution reactions that involve both processes. The precise understanding of the mechanism and dynamics of the photogeneration of carbocations and carbon radicals is therefore an important quest. In particular, the role of electron transfer for the generation of carbocations from the radical pair is still unclear. A quantitative femtosecond absorption study is presented, with ultrabroad probing on selected donor and acceptor substituted benzhydryl chlorides irradiated with 270 nm (35 fs) pulses. The ultrafast bond cleavage within 300 fs is almost exclusively homolytic, thus leading to a radical pair. The carbocations observable in the nanosecond regime are generated from these radicals by electron transfer from the benzhydryl to the chlorine radical within the first tens of picoseconds. Their concentration is reduced by geminate recombination within hundreds of picoseconds. In moderately polar solvents this depletion almost extinguishes the cation population; in highly polar solvents free ions are still observable on the nanosecond timescale. The explanation of the experimental findings requires the microscopic realm of the intermediates to be accounted for, including their spatial and environmental distributions. The distance dependent electron transfer described by Marcus theory is combined with Smoluchowski diffusion. The depletion of the radical pair distribution at small distances causes a temporal increase of the mean distance and the observed stretched exponential electron transfer. A close accord with experiment can only be reached for a broad distribution of the nascent radical pairs. The increase in the inter‐radical and inter‐ion pair distance is measured directly as a shift of the UV/Vis absorption of the products. The results demonstrate that, at least for aprotic solvents, traditional descriptions of reaction mechanisms based on the concept of contact and solvent‐separated pairs have to be reassessed.